If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 5) = 64 Reorder the terms: 5(5 + x) = 64 (5 * 5 + x * 5) = 64 (25 + 5x) = 64 Solving 25 + 5x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 5x = 64 + -25 Combine like terms: 25 + -25 = 0 0 + 5x = 64 + -25 5x = 64 + -25 Combine like terms: 64 + -25 = 39 5x = 39 Divide each side by '5'. x = 7.8 Simplifying x = 7.8
| 3(2f-6)+6=36 | | 3n+2(4n-5)-7+n= | | -6x+2x=3x | | x=6x^7+35x^6-169x^5-612x^4+1823x^3+1215x^2-2758x-980 | | 7x+31=91 | | 2x+3=3+2 | | b+3b=56 | | -(1+4x)=3-(3x-3) | | 7y-2=-8-32 | | 2x+8y=12 | | 879+56.23+1.92= | | 2(6)=5x+2 | | -5(t-3)+8t=7t-3 | | (2x+k)(x-2k)=2x^2+9x-18 | | .5x-1.7=.3x-1 | | 10X-30=360 | | f(-3)=x^3+5 | | 5e-2(4-3e)-2e=10 | | -4.3-2*13.2= | | .5x-1.7=.3-1 | | 4p-13=3p-9 | | Q=7(3.14)v | | -6c-3(c+7)=24 | | -4.3-2(13.2)= | | 126m^2-113-63= | | 5n-2(n-2)=12 | | 2x^2-x+11=0 | | 4n=24n-20-3 | | 6x+8y=54 | | (3/5)=(1/3)+f | | 6x-2(x-1)=-3+7x+11 | | -5n-(-3-3n)=-4 |